Pengaruh faktor psikososial terhadap burnout dalam kalangan paramedik di hospital negeri Kelantan - Mohd Fadli, Shaari (2024)
Burnout among paramedics in Malaysia is an issue that is getting more and more attention, especially with the high work pressure in the health sector. Burnout among workers, including the health sector, has become a research topic that is gaining more and more attention in Malaysia, especially among paramedics. Those working in emergency services are reported to face high levels of burnout, with symptoms of emotional exhaustion, depersonalization (feeling alienated from work), and reduced personal achievement. The stress of emergency situations and excessive workload are the main causes. Therefore, a cross-sectional study was conducted to investigate the level of burnout and the relationship between job demands, work pressure and social support with burnout among paramedics in the state of Kelantan. This study uses a quantitative method by distributing a questionnaire containing 76 questions, which consists of instruments selected to measure burnout, job demands, work pressure and social support to 108 respondents in the Emergency and Trauma Department from 2 large specialist hospitals in the state of Kelantan, namely Raja Perempuan Zainab II Hospital, Kota Bharu and Sultan Ismail Petra Hospital, Kuala Krai. These two hospitals were chosen as study locations due to the highest number of patient arrivals in the state of Kelantan. The results of the survey found that the level of burnout among paramedics in hospitals in the state of Kelantan is moderate. In addition, there is a significant relationship between job demands and job stress with burnout. However, there is no significant relationship between social support and burnout. Therefore, in order to control the effects of job demands and work pressure, this study suggests the implementation of the Total Wellness and Health Promotion (TWHP) program, because it can provide a more holistic approach to paramedics in curbing the problem of burnout from continuing.